Seizing this COVID moment: What can Food Justice learn from Disability Justice? - Martha Stiegman (Canadian Food Studies, 2022)
It is now a shameful truism that COVID-19 functioned as a big reveal, exposing, and amplifying the structural inequalities Canadian society is built upon. We are now a year and a half into the global pandemic. I am writing from Toronto, where “hot spots” (neighbourhoods with high infection rates) is code for racial and economic inequality (Wallace 2021) and public health guidelines have rendered low income “essential workers” disposable, amidst ballooning food insecurity rates, especially in low-income racialized communities (Toronto Foundation 2020; CBC News 2020). We are all in the same storm but in very different boats, as the new saying goes. I want to suggest that this moment, as Canadians are poised to step out of lockdown and return to ‘normal’, is a particularly useful one for Food Studies to consider what we could learn from Disability Justice movements in order to address a glaring hole in our collective scholarship and analysis.